PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PEMBANGUNAN RUMAH OLEH DEVELOPER YANG TIDAK SESUAI DENGAN STANDAR DAN KUALITAS PADA KASUS CINDO RESIDENCE DALAM PUTUSAN PENGADILAN TINGGI PALEMBANG NOMOR 94/PDT/2012/PT.PLG (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2022)
The house as a place to live has developed not only as one of the primary needs for humans in addition to clothing and food but also as a marker of one's welfare. The need for quality housing can be a symbol that people's lives are also of quality in the sense of being prosperous and prosperous. The process of building a house is not cheap. Departing from this fact, housing developers have emerged to answer the community's need for a house as a place to live but have not been able to provide enough money to build the desired house themselves. However, there are developers who build houses that are not in accordance with the standards and quality expected by consumers. The writing method used in this paper is using the normative legal writing method. In this normative legal writing method, two approaches are used, namely the conceptual approach and the statutory approach. Regarding unlawful acts in the process of buying and selling housing, it can be seen from several aspects, namely the existence of an act, the act is an unlawful act, there is an error on the part of the perpetrator, the emergence of a loss for the victim, between the loss suffered by the victim and the error on the part of the perpetrator has causality. Cindo Residence housing developers in completing the house construction process are not in accordance with the standards and quality expected by consumers which cause harm to the consumer, which is known when the building has been completed and occupied. Both in disputes of unlawful acts and defaults, consumers generally demand compensation for damage, pollution and/or those who suffer losses due to consuming goods and/or utilizing services. Settlement of consumer disputes can be resolved through the courts or through alternative dispute resolution channels.